The main inventions for technologies of the magnetic-pulsed attraction of the sheet metals. A brief review - Batygin, Yu.V.; Chaplygin, E.A.; Shinderuk, S.A.; Strelnikova, V.A. (Електротехніка і електромеханіка, 2018)
Purpose. The description of the Equipment for the Magnetic-Pulsed Attraction (or EMF-attraction) of the sheet metals which allows
non-contact deforming of ferromagnetics (the low carbon steels, for example), the non-magnetic billets from aluminium alloys and the
practical realization of the new advanced technologies in the modern processing manufacture. Methodology. Comparative analysis of
characteristics and operating conditions of the systems under consideration. Results. Physically, all magnetic-pulsed methods of attraction are based on the Lorentz repelling forces decreasing and on increasing the attracting forces when the sheet billets being deformed
are transparent for the low working frequency acting electromagnetic fields. The ferromagnetic samples attraction is caused by their
magnetic properties. For the non-magnetic metals attraction an accessory conducting screen is being introduced in construction of the
inductor system which is the method tool. In this case the attraction effect is caused by the force interaction of the unidirectional currents
induced in the screen and in sheet billet. The different constructions of the attracting tools attended for fulfilling the different production
operations (for example, it can be stamping, flattening etc.) with metals owning by different electrophysical properties are represented.
Originality. The novelties in the magnetic pulsed installations used as the power sources in the complex equipment for the automobile
bodies repair are given. Practical value. The practical application of the elaborated systems for the dents removing in the sheet metals are
suggested and successfully approbated. In the whole these works can be considered as new scientific direction and used for different
manufacturing aims though the main attention is paid to the practical application in the field of the automobile bodies repair. The most
part of the described inventions is defended by the Ukrainian Patents (23 from total quantity – 33 References) and little known to the west
specialists in the area of the magnetic pulsed technologies. From the authors view point this is a main particularity and usefulness of the
present paper. В статье описано оборудование, предназначенное для магнитно-импульсного притяжения листовых металлов, которое
позволяет бесконтактное деформирование, как ферромагнетиков, так и немагнитных заготовок из алюминиевых сплавов
и практического применения новых передовых технологий в современной индустрии. Притяжение ферромагнитных образцов обусловлено их магнитными свойствами. Для притяжения немагнитных металлов в конструкцию индукторной системы, являющейся инструментом метода, вводится вспомогательный проводящий экран. Представлены различные конструкции инструментов притяжения для выполнения различных производственных операций по обработке металлов,
обладающих различными электрофизическими свойствами. Описана новизна магнитно-импульсных установок, используемых в качестве источников энергии в комплексах оборудовании для ремонта автомобильных кузовов.